Children and their development - Kail, Robert V. (Pearson Education/Prentice Hall, 2007)
[This text] uses[s] fundamental developmental issues as a foundation for integrating the many discoveries that make child-development science a dynamic field. [It] explain[s] many different methods used by researchers, then illustrate[s] them repeatedly to drive home the lesson that progresses when complementary methods coverage. [It also] demonstrate[s] that the results of child-development research can be used to enhance the lives of children and their families. -Pref